Bacterial contamination of eggs and behaviour of poultry flocks in the free range environment. (December 2016) - Moyle, Talia; Drake, Kelly; Gole, Vaibhav; Chousalkar, Kapil; Hazel, Susan
Highlights: Significant effect of hen age on total bacterial levels on the egg shell surface. Hen age had a significant effect on the level of total bacteria in egg shell pores. Escherichia coli were the most frequently isolated Enterobacteriaceae species. Significant effect of hen age on feather condition score. Significant effect of hen age on submissive/crouching behaviour. Abstract: The free range production system is becoming more common in Australia and is expected to increase. Free range hens are exposed to more stressors in comparison to hens from barn and cage systems and it is suggested that stress can increase bacterial shedding on eggs. The aims of this study were to examine the level of total bacteria and Enterobacteriaceae populations, as well as the presence of Salmonella and Campylobacter, in eggs collected from two free range flocks on two different farms and to conduct longitudinal observations of the behaviour and welfare of hens in the free range production system. Hen age (weeks) was shown to have a significant effect (increase) on the level of total bacteria on the egg shell surface and in shell pores, as well as having an effect on feather condition score. As the hens aged, the frequency of external visual egg characteristics increased, as did feather condition score (where feather condition was poorer). These observations indicate areas which should be investigated further to improve the food safety of eggs and optimise the welfare of free range hens.